MACROECONOMIC DETERMINANTS OF STOCK RETURNS IN PAKISTAN: THE CASE OF KARACHI STOCK EXCHANGE - SOHAIL, Nadeem; ZAKIR, Hussain (Journal of Advanced Studies in Finance, 2010)
The stock market is one of the imperative indicators of the economy. This study strived to explore the impact of five macroeconomic variables on General Index in the long run and short run. In order to investigate the long run and short run relationships Johansen cointegation technique and VECM was applied. This study used monthly data from November 1991 to June 2008 for analysing General Index. The study revealed that consumer price index, and real effective exchange rate, and industrial production index had a positive impact on stock prices in Pakistan while money supply and three month treasury bills rate affected stock prices negatively in the long run. The VECM demonstrated that it took more than eight months to eliminate the disequilibrium. The variance decompositions exposed that consumer price index and money supply showed greater forecast error than real effective exchange rate, industrial production index, and three month treasury bills rate for General Index.